PENDIDIKAN TAREKAT AT-TIJANI DI KABUPATEN JEMBER - Sholeh, Badrus; Rizal, Syaiful (International Conference on Humanity Education and Society (ICHES), 2024)
At-Tijani Tarekat education is one of the Sufism education processes carried out in Sumber Lesung Village, Ledokombo District, Jember Regency. The congregation was very enthusiastic about participating in this activity. This research aims to describe the education of the At-Tijani Congregation in Sumber Lesung Village. This research approach uses qualitative with descriptive research type. The results of the research show that the implementation of Tarekat At-Tijani education is carried out through providing materials/practices and practices of the Tarekat Tijaniyah to the congregation. The material and practices of the Tarekat Tijaniyah are in the form of wirid ordinaryah, wazifah, and hailalah. The core material and practices of the practice are istigfar and sholawat. The implementation of this tarekat education is carried out as an effort to follow the commands of Allah SWT by increasing the reading of istghfar, sholawat and monotheism sentences. The aim of this education is to create Sufistic values ​​in humans so that they become humans who have a good personality, have good morals, are steadfast in worship, and are able to maintain good relationships with fellow humans (wahablun minannass) and good relationships with Allah SWT (hablun minallah)